Hubungan Breastfeeding Self-Efficacy (BSEF) dengan Pemberian ASI Eksklusif - Fadilla Maharani; Enny Yuliaswati (Jurnal Anestesi, 2024)
Background: In Central Java province, the percentage of infants aged 0-23 months who are breastfed in Sukaharjo district in 2021, which is an average of 10.40%, is still in the low category of exclusive breastfeeding (BPS, 2021). Exclusive breastfeeding during this period, then continued with complementary foods until the age of 2 years (WHO, 2018). The low exclusive breastfeeding is caused by several factors, one of which is the mother's self-efficacy. Mothers with high levels of breastfeeding self-efficacy have a greater tendency to start and continue breastfeeding their babies. Objective: This study aims to determine the relationship between Breastfeeding Self-Efficacy and exclusive breastfeeding. Methods: This study is a quantitative study with the type of Correlational Analysis. The design used in this study is cross sectional. In this study, the sample used was as many as 35 respondents, the analysis test used in this study was the Chi Square Test to determine the relationship between BSEF and exclusive breastfeeding. Results: The results of the chi square test obtained a significant relationship of 0.000 where Asymp. Sig 0.05 so it can be concluded that Ha is accepted and Ho is rejected, which means that there is a relationship between breastfeeding self-efficacy and exclusive breastfeeding. Conclusion: this study concluded that there is a significant relationship between Breastfeeding Self-Efficacy and exclusive breastfeeding.